The Iberian crusaderism and the end of Pax Islamica in the Indian Ocean - Kopanski, Ataullah Bogdan (2009)
The Christian European corsairs andpirates cruised against Muslim sea merchants in the Indian Ocean with the spiritual blessing of the powerful churches in Portugal, Spain, Netherlands, England and France. Their conquests ofthe prosperous Muslim seaports in the Indian Ocean were authorized by the royal courts ofthe new western powers and the militant religious orders The Iberian sea rovers were formidable rogues of western Christendom waging the first global naval anti-Islamic crusade in the new Era ofGunpowder. The commercial interests of Islamic states were extensively damaged by Portuguese and Spanish intercontinental prowlers who operatedfrom hidden harbors ofsmall oceanic islands located between the southern coasts of Africa and Malay Archipelago. The Protestant English and Dutch 'Honourable and Grandest' Companies ofEast India trading spices, emerged as the most powerful enterprises from the oceanic war ofattrition against the equally acquisitive Portuguese, French and Spanish seafaring 'papists '. While he Malay sea trade and Gujarati costal trade suffered substantial loses, it was the South Arabia which lost its dominant role in the oceanic commerce. Arabia Felix became 'Ireland' of the Islamic South in the Golden Age ofEuropiracy. The author examines the historical geography ofclash ofreligions and economies in the Maritime Afrasia.